2003
DOI: 10.1210/en.2002-220933
|View full text |Cite
|
Sign up to set email alerts
|

Novel Neurotrophin-1/B Cell-Stimulating Factor-3 (Cardiotrophin-Like Cytokine) Stimulates Corticotroph Function via a Signal Transducer and Activator of Transcription-Dependent Mechanism Negatively Regulated by Suppressor of Cytokine Signaling-3

Abstract: Novel neurotrophin-1/B cell-stimulating factor-3 (NNT-1/BSF-3) is a recently cloned gp130 cytokine, acting through the tripartite ciliary neurotrophic factor receptor (CNTFR) alpha/leukemia inhibitory factor receptor (LIFR)/gp130 receptor complex. The aim of the current study was to investigate the role of NNT-1/BSF-3 in corticotroph cell function and further characterize NNT-1/BSF-3 signaling pathways. Using RT-PCR, expression of ciliary neurotrophic factor receptor alpha, leukemia inhibitory factor receptor,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…36 Consistently, we demonstrated that SOCS3 can also inhibit signalling of other STAT activating cytokines. [37][38][39][40][41][42] IL31Ra belongs to the IL6 cytokine receptor (IL6R) family. IL6Rs have divergent effects on cell proliferation in different epithelial cell types.…”
Section: Discussionmentioning
confidence: 99%
“…36 Consistently, we demonstrated that SOCS3 can also inhibit signalling of other STAT activating cytokines. [37][38][39][40][41][42] IL31Ra belongs to the IL6 cytokine receptor (IL6R) family. IL6Rs have divergent effects on cell proliferation in different epithelial cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the role of STAT-dependent suppressor of cytokine signaling (SOCS)-3 gene expression and its role as an endogenous negative regulator of cytokine-induced corticotroph function has been examined by experiments using LIF as a corticotroph stimulus [6]. Stimulatory effects on corticotroph cell function in vitro have also been described for human OSM (hOSM) [7][8][9][10][11], CNTF and NNT-1/BSF-3 [12], IL-6 [13][14][15][16] and IL-11 [17], respectively. However, as these effects have been investigated under various conditions, these studies cannot show the relative potency of each gp130 cytokine in corticotroph function.…”
Section: Introductionmentioning
confidence: 99%
“…SOCS-3 proteins have been shown to play a role in both leptin resistance (40) and insulin resistance (41). Interestingly, SOCS-3 is induced by all known gp130 cytokines (32,33,(42)(43)(44)(45)(46)(47), as well as additional hormones, including insulin (48), growth hormone (49), and leptin (50). However, many inducers of SOCS-3, including CTNF, do not induce insulin resistance.…”
Section: Discussionmentioning
confidence: 99%